Pseudo-Differential Frequency Filter Using Conveyors - Milota, Martin (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
The author of this article deals with the design and analysis of a pseudo-differential filter. This designed filter works in voltage mode and is a second-order low pass filter. The filter uses three current conveyors and four passive elements. The proposed circuit reaches the theoretical values in simulations. The simulation results are displayed by modular and phase characteristics.
Keywords: conveyors; voltage mode; pseudo-differential filter; frequency filter; second order; lowpass; modular characteristic; phase characteristic